Assessment of knowledge and practice of Baghdadi pediatricians regarding the management of neonatal hyperbilirubinemia - Hameed, Numan N.; abdul razak, Omar H. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Management of hyperbilirubinemia remains a challenge for neonatal medicine because of the risk for serious neurological complications related to the toxicity of bilirubin.Objectives: This study aimed to assess the knowledge and practice of a sample of Baghdadi pediatricians regarding the risk factors, management of hyperbilirubinemia.Subjects and Methods: This survey study was conducted from 1st of March 2011 to 31st December 2011, 10 questions questionnaire was handled to a random sample of 100 Arab and Iraqi board certified pediatricians in Baghdad who is working in governmental hospitals and/or in private sector. These questions include various aspects of neonatal hyperbilirubinemia management.Results: Thirty four percent of pediatricians had 5-10 years of practice since completion of residency, 54% of pediatricians serve about 50 -100 neonates / year (P < 0.001), 60% of physicians manage 15 mg/dl need phototherapy (P= 0.0001), 56% of pediatricians regarded a TSB level of 20 mg/dl in 25-48 hours of life need exchange transfusion if phototherapy failed ( P=0.000), 76% believed “to a very high degree” that jaundice presenting in the first 24 hours is a significant risk factor for the development of hyperbilirubinemia in term infants, 44% believed that the post-discharge TSB follow up is vital to lower the incidence of neurologic complication, while 56% thought it would not affect the prognosis (P = 0.12).Conclusions: Most Baghdadi pediatricians devitalize the post- discharge follow up of TSB and underestimate its role in decreasing the incidence of undiagnosed neonatal jaundice, and they thought that severe hyperbilirubinemia and kernicterus should be in the first place a concern of PHCs.